INTERFERENCE OF COMMUNICATIVE NORMS IN BILINGUAL CONDITIONS - Majidova Feruza Islom kizi (Web of Journals Publishing, 2024)
This article discusses about the study of compatibility from the standpoint of interference seems extremely important, since it allows us to solve a number of both methodological and linguistic problems. It is widely proved that in linguistic studies, different types of combinability are considered separately. In practice, the assimilation of norms of different types of compatibility - grammatical, lexical, semantic - occurs simultaneously, in interconnection. Therefore, it is very important to comprehensively study compatibility in order to overcome interference, which allows us to take into account the conditions, reasons, levels of language and other extra- and intralinguistic factors that influence the successful acquisition of combinability norms in a non-native language.
Keywords: interference, bilingualism, modern linguistic, speech communication, semantic, phenomenon.